National grassland mapping in Hungary: an overview - Belényesi, Márta; Pacskó, Vivien; Lehoczki, Róbert; Pataki, Róbert; Tanács, Eszter; Kristóf, Dániel; Szekeres, Ádám; Zsembery, Zita; Mikus, Gábor (JOURNAL OF LANDSCAPE ECOLOGY, 2025)
Knowing the extent and condition of grasslands and related habitats, as well as their monitoring, is an issue that is increasingly coming to the fore. In Hungary, similar to other European countries, several fields of expertise would need information on the extent, ecological condition, yield, etc., regarding different grassland types to be available in a unified, transparent and regularly updated database. Such a database would provide a long-term and beneficial solution for planning, implementing and monitoring the methods of preservation, maintenance and utilization. Currently, there is no spatial database that could meet all these needs, especially not at the national level in Hungary. However, several data and spatial data provide information on land cover and/or land use from different perspectives that could serve as a good starting point to build such a system. We aim to present some of these data, the land cover maps produced by the Lechner Knowledge Centre in particular. A comparison of the databases presented reveals that it is not easy to answer even the question regarding the exact area of Hungarian grasslands. It is due, among other things, to the fact that the databases are created for different purposes with different methodologies and nomenclature. However, the experience that has been gained in the development of these and similar databases can be very useful for building a concept for the establishment of a grassland register in Hungary.
Keywords: land cover mapping; grassland; spatial database; remote sensing